Multidisciplinary Research at Grasshopper Pueblo, Arizona - Longacre, William A.; Holbrook, Sally J.; Graves, Michael W. (University of Arizona Press, 1982)
"For the past twenty years the University of Arizona's archaeological field school has been conducting research focused on Grasshopper Pueblo, a large, fourteenth-century Western Anasazi site, located below the Mogollon Rim, on the Fort Apache Reservation, in Arizona. . . . Research questions pursued at Grasshopper involve explicating the founding, growth, and abandonment of the site within the context of three broad areas of causality. These are environmental and climactic change; regional and interregional economics, especially trade; and subsistence change, including agricultural intensification. The papers in this volume . . . are presented as specialized contributions to this work."-Journal of Anthropological Research Contributors: Larry D. Agenbroad Eric J. Arnould Walter H. Birkby Vorsila L. Bohrer Jeffrey S. Dean Michael W. Graves Sally J. Holbrook Gerald K. Kelso William A. Longacre Charmion R. McKusick J. Jefferson Reid John W. Olsen Stanley J. Olsen William Reynolds William J. Robinson Izumi Shimada Stephanie M. Whittlesey David R. Wilcox